The lean canvas business model training for members of the Indonesian laundry entrepreneurs association (HIPLI) - Kurniawan, Wawan; Suhardini, Didien; Triwulandari, Triwulandari; Sari, Emilia; Habyba, Anik Nur (Community Empowerment, 2021)
Community Service Partners are members of the Indonesian Laundry Entrepreneurs Association (HIPLI). This Student Creativity Program (PKM) activity is intended to provide a thorough explanation of the Lean Canvas model, business opportunity theory, appropriate market strategies, and risk analysis for business owners that are members of HIPLI. The participants were trained using presentation and discussion techniques. The feedback from the participants through the questionnaires showed that they were satisfied with the training’s implementation. Finally, this PKM implementation concluded that the Lean Canvas Business Model Training for HIPLI entrepreneurs provided a better understanding of the training material such that participants are more enthusiastic about continuing their business.